PERAN MANAJERIAL KEPALA SEKOLAH DASAR DALAM MENINGKATKAN KREATIVITAS PEMBELAJARAN BAGI GURU - Nurul Annisa Safitri; Darsinah Darsinah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
The principal of the elementary school is the leader in thw basic education unit whose task is to carry out the management of the elementary education unit he leads. The principal of the elementary school is the leader in the basic education unit whose task is to carry out the management of the basic education unit he leads. A good principal can shape the learning carried out by teachers is also good, resulting in good student and teacher achievement. The role of the principal as a manager can assist in increasing the creativity of teaching teachers to produce quality students. This study aims to describe the principal’s strategy in planning programs, organizing, mobilizing and supervising school programs in increasing learning creativity for teachers. This research is a case study using a qualitative descriptive approach. Data was collected by means of observation, inteviews and documentation. The results of this study indicate that the managerial role of elementary school principals in increasing learning creativity for teachers has been going well with the roles og: (1) planning an activity program bu detailing the needs of students and education personnel, planning a curriculum that will run well, and creating a cultural climate that conducive; (2) create an organizational structure that involves parents through the school committee and completes the necessary infrastructure; (3) setting a good and calm example at work, motivating and rewarding personnel both morally and materially, improving welfare and involving educational staff in training; (4) leading and supervising in order to improve the school goals that were formulated together.